Content Analysis of Higher Order Thinking Skills (HOTS) in the E-Module of Lecturers at Muhammadiyah University of North Sumatra - Mariati, Mariati; Saehu, Uun Ahmad; Hani, Syafrida (Budapest International Research and Critics University, 2021)
The purpose of this study is to analyze the content of HOTS in E-modules that have been developed by lecturers, especially those related to accounting special skills courses. This analysis is based on the criteria for teaching materials containing higher-order thinking skills for students, especially the questions that have been developed in the module. This research uses content analysis method with stages of data reduction, data presentation and conclusion drawing. Data was collected using an assessment rubric according to the cognitive level with HOTS characteristics starting from the level of analysis (C4), Evaluation (C5) and Creation (C6), then presented in graphic form. The source of data in this study is the E-module which has been developed by the lecturer.